2016
DOI: 10.3389/fpls.2015.01223
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Maize psbA Gene Enhances Drought Tolerance Through Regulating Antioxidant System, Photosynthetic Capability, and Stress Defense Gene Expression in Tobacco

Abstract: The psbA (encoding D1 protein) plays an important role in protecting photosystem II (PSII) from oxidative damage in higher plants. In our previous study, the role of the psbA from maize (Zea mays. L) in response to SO2 stress was characterized. To date, information about the involvement of the psbA gene in drought response is scarce. Here we found that overexpression (OE) of ZmpsbA showed increased D1 protein abundance and enhanced drought stress tolerance in tobacco. The drought-tolerant phenotypes of the OE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 47 publications
4
62
0
Order By: Relevance
“…In addition, psbA protects photosystem II from oxidative stress developed through drought. A previous report of Huo et al [60] demonstrated that the overexpression of the psbA gene improves drought tolerance in tobacco plant. The occurrence of psbA in B .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, psbA protects photosystem II from oxidative stress developed through drought. A previous report of Huo et al [60] demonstrated that the overexpression of the psbA gene improves drought tolerance in tobacco plant. The occurrence of psbA in B .…”
Section: Resultsmentioning
confidence: 99%
“…While most photosynthesis‐related genes were downregulated after dehydration, especially in TPs, several photosynthesis‐related genes were upregulated, such as PsbA , PsbE , PsbN and Psb29.4 (Figure S3). These genes were upregulated probably for self‐protection, such as oxidation detoxification, recovery from photoinhibition and response to excess light (Keren et al ., ; Torabi et al ., ; Sugiura et al ., ; Huo et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…MDA content was determined as described previously (Draper and Hadley, 1990; Huo et al, 2016). H 2 O 2 content was assayed according to our previously used method (Xia et al, 2012).…”
Section: Methodsmentioning
confidence: 99%